The influence of the cassava mealybug Phenacoccus manihoti Mat. Ferr. (Hom., Pseudococcidae) on yield formation of cassava, Manifhoti esculenta Crantz - Schulthess, F.; Baumgaertner, J.U.; Delucchi, V.; Gutiérrez, A.P (Wiley, 1991)
The cassava mealybug (CM), Phenacoccus manihoti Mat.‐Ferr., is a dry season pest of cassava, Manihot esculenta Crantz. Its effects on the patterns of dry matter production and allocation in cassava planted July, September 1982 and May 1983 and grown for 12 months was studied. Peak CM population densities varied greatly (from 600 to 37000 CM per plant) due to plant size at the time of infestation, duration of infestation, and mortality from the introduced parasitoid Fpidinocarsis lopezi (De Santis). CM feeding reduced new leaf production and assimilation and allocation of dry matter to storage roots. Severly infested cassava plants, lost between 9 % and 46 % during the dry season, compared to CM‐free plants. At the beginning of the ensuing rainy season, mobilisation of reserves from storage roots for regrowth caused temporary root yield losses of up to 75%. Yield losses at harvest across planting dates measured 12 months after planting, were of 52 to 58 % in the CM‐infested plants compared to noninfested plants.